Pharmacological action and Properties of Swasahara Mahakashaya in Swasa Roga: A Review. - Sharma, Pariksha; Pandey, Yogesh Kumar; Kumar, Akshay (International Research Journal of Ayurveda & Yoga, 2023)
Swasa (Dyspnoea) is a Yapya vyadi (incurable but manageable) with Sthana Sanshraya (stage of localization) and Adhisthana (seat) as Pranavaha Srotas (respiratory channel). In modern medicine, it broadly involves lungs and heart as main site of pathology. They generally involve infective, allergic, genetic, occupational aetiology. So, the drug or group of drugs which act directly on Pranvaha Srotas, or on the disease will help in alleviation of disease. Charak mentioned these drugs as Swasahara Mahakashaya, a group of ten drugs which have direct action on the disease. This review will focus on establishing the action of these drugs on various conditions resulting in Dyspnoea as a prominent symptom. It will explore various causes of dyspnoea and factors responsible for dyspnoea, along with ayurvedic properties as well as pharmacological action of various active components of each individual drug on cellular level.